Pleasured by you - Wright, Elle (Wright, Elle. Wellspring series., 2018)
It<U+2019>s been years since Bryson Wells cut all ties to his hometown and family, going so far as to change his name and delete his social media accounts. He<U+2019>s built a profession and a life for himself away from his domineering father, but as the man<U+2019>s death draws near, Bryson finds himself back in Wellspring<U+2014>and face to face with the woman who has a hold on his heart . . . Jordan Clark<U+2019>s life is not turning out quite as she planned. Instead of working towards her law degree, she<U+2019>s in Wellspring caring for her ailing grandfather. Running into Bryson in the hospital brings back memories of the night their longtime friendship erupted into passion. The attraction between them has only gotten stronger. But Jordan will have to decide if Bryson<U+2019>s love is real, or if he<U+2019>s settling to get the family he<U+2019>s always wanted. . .